Quantum Mind Theory in International Relations: Between Illusion and Science - Skurdauskaitė, Ieva (Politologija, 2018)
[only abstract in English; full article, abstract in Lithuanian]Since the 19th century, social sciences have been dominated by positivist thinking, which is based on the Newtonian worldview and implies mechanistic, deterministic, materialistic and atomistic methodological tools for conducting researches. However, this Newtonian worldview can not explain the phenomenon of consciousness and thus leaves the scientists with the unresolved body-mind problem. The solution has been recently offered by quantum theory, which challenges the classical thinking by completely changing its ontology, or, to be more precise, which aims at unifying social and physical ontology and laying the ground for the minded matter. In one of the most recent and prominent scholarly books, written by A. Wendt and titled Quantum Mind and Social Science: Unifying Physical and Social Ontology, the author claims that consciousness is a quantum mechanical phenomena and that all of us are in fact a walking wave function. If that is true, then human society must also have quantum qualities. Even though A. Wendt offers a solution to one of the long-lasting questions of social science, he leaves us without any explanations of how the theory might impact the discipline of international relations.Therefore, this paper is focused on 3 questions: 1) How does quantum mind theory challenge positivist thinking in international relations? 2) How does it broaden/narrow our current understanding of international relations – namely, what is the relationship between quantum mind theory and other postpositivism theories? 3) How does quantum mind theory impact international relations? An analysis of the challenges posed to classical thinking and a comparison of the differences and similarities with critical theory, postmodernism and constructivism revealed that quantum mind theory is not yet a new social sciences paradigm or a valid independent theory, but that it could be used as a theoretical tool of postmodernism. The main reasons involve a lack of empirical researches, scholarly supporters and consistent epistemological logic. On the other hand, there are a variety of objects and discussions in international relations that can be analyzed using quantum mind theory: quantum entanglement through language, global society and the collective mind, terrorism and the impact it has on global conflicts and communication, quantum diplomacy and others. The implementation of quantum theory principles – quantum coherence, superposition, quantum entanglement, wave and particle duality and uncertainty – into researches of international relations provides scholars with the perspectives of explaining the changing nature of a global world, new unpredictable threats and global communication.
Keywords: none